Centering Pregnancy in Missouri: A System Level Analysis - Pamela K. Xaverius; Mary Alice Grady (The Scientific World Journal)
Background. Centering Pregnancy (CP) is an effective method of delivering prenatal care, yet providers have been slow to adopt the CP model. Our main hypothesis is that a site’s adoption of CP is contingent upon knowledge of the CP, characteristics health care personnel, anticipated patient impact, and system readiness. Methods. Using a matched, pretest-posttest, observational design, 223 people completed pretest and posttest surveys. Our analysis included the effect of the seminar on the groups’ knowledge of CP essential elements, barriers to prenatal care, and perceived value of CP to the patients and to the system of care. Results. Before the CP Seminar only 34% of respondents were aware of the model, while knowledge significantly after the Seminar. The three greatest improvements were in understanding that the group is conducted in a circle, the health assessment occurs in the group space, and a facilitative leadership style is used. Child care, transportation, and language issues were the top three barriers. The greatest improvements reported for patients included improvements in timeliness, patient-centeredness and efficiency, although readiness for adoption was influenced by costs, resources, and expertise. Discussion. Readiness to adopt CP will require support for the start-up and sustainability of this model.